IMF Staff Papers, Volume 52, No. 2. (IMF Staff Papers; IMF Staff Papers ;, 2005)
This paper examines contractionary currency crashes in developing countries. It explores the causes of India's productivity surge around 1980, more than a decade before serious economic reforms were initiated. The paper finds evidence that the trigger may have been an attitudinal shift by the government in the early 1980s that, unlike the reforms of the 1990s, was pro-business rather than pro-market in character, favoring the interests of existing businesses rather than new entrants or consumers. A relatively small shift elicited a large productivity response, because India was far away from its income possibility frontier.